Market intelligence to understand groundnut preferences among Tanzanian farmers: A data-driven approach shows that gender is not the only factor behind farmer choice of crop variety - 1000FARMS Platform; de Sousa, Kaue (2025)
This poster presents a data-driven success story from the 1000FARMS platform in Tanzania, where participatory on-farm testing (tricot) was combined with socio-economic segmentation to better understand how farmers select groundnut varieties. Rather than analyzing preferences solely by gender, the team led by the Tanzania Agricultural Research Institute and CIMMYT identified three distinct farmer segments based on production roles, market access, and experience. Over four growing seasons, 1,805 farmers tested 57 varieties, and their feedback led to the release of two new groundnut varieties. The results challenge simplistic assumptions and demonstrate the importance of experience, economic roles, and market access in shaping varietal preferences. This work shows how integrating farmer-centered data into breeding can generate more inclusive outcomes and targeted innovation.